Analysis and Design of Data Mart Decision Support Systems at PT Marlindo Tirta Nusantara - Sudradjat, Budi (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The role of information technology in each company is very influential in providing complete and accurate information. With a data warehouse or data mart the company can utilize important asset data to present the information needed.. Shipping firms nowadays are in operation with extremely competitive and challenging environment. Vast volume of knowledge is generated from various operational systems and these are used for determination of several business issues that needed imperative handling. The results obtained from this study are data marts that simplify and accelerate the provision of data and information to support decision making, so as to provide a basis for developing DSS and EIS applications. Conclusions obtained by the data warehouse or data mart can provide complete, accurate and integrated information as a basis for consideration for the executive in making decisions so that decisions taken are based on real facts owned by the company.